A Comparison of the Structural Elements of the Integrated Reporting and the Management Report - Bezverkhiy, K. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
A new type of reporting has been introduced both in the international and Ukrainian practice: the integrated reporting and the management report. The integrated reporting in Ukraine is not subject to regulation by central government, whereas the structure and format of the management report is legally fixed (the Law of Ukraine “Accounting and Financial Reporting in Ukraine). However, as of 01.12.2018, a unified format for the management report was not approved by the Ministry of Finance of Ukraine. According to the abovementioned Law of Ukraine, micro-enterprises and small enterprises are exempt from the management report, whereas medium enterprises are not obliged to show non-financial data in the management report. The integrated reporting can be submitted separately from the financial reporting, but, following the above Law of Ukraine, the management report is to be submitted together with the financial statement and the consolidated financial reporting in the legally fixed procedure and time limits. The purpose of the study is to compare the structural elements of the integrated reporting according to the International Integrated Reporting Framework, the management report according to the Draft Methodical Recommendations on Compilation of Management Report by the Ministry of Finance of Ukraine, and the management report according to the Draft Methodical Recommendations on Preparation of Report from Kreston GCG, in order to identify their differences and the feasibility of their simultaneous application in the national reporting practice. Based on the analysis, the main differences between the Integrated Reporting and the Management Report are highlighted. A comparative analysis of the structural elements of the integrated reporting and the management report is conducted, to find out the correlation of their structural elements. It is demonstrated that the differences between the integrated reporting and the management report are negligible; it is, therefore, recommended to combine these two types of reporting in one optimal format.